Parkinson Disease and Its Clinical Manifestations - Olegário, Raphael Lopes; Fobbs, Jerrime Bernard; Lopes, Bruno Sousa; Strini, Paulinne Junqueira Silva Andresen; Strini, Polyanne Junqueira Silva Andresen; de Melo, Lídia Mara Aguiar Bezerra (Revista de Medicina e Saúde de Brasília, 2019)
Parkinson's disease (PD) is a neurodegenerative disorder that leads to progressive deterioration of motor function due to loss of dopamine-producing brain cells. Symptoms generally develop slowly over years. The progression of symptoms varies from person-to-person due to the diversity of the disease. Although there is no cure yet, multiple treatment options ranging from prescription dispensing, disease management and/or medication therapy management and surgery exists as a means to help patients living with this disease. Parkinson’s itself is not fatal, however, complications that arise as consequence of this disorder can be serious. The diagnosis of PD within a patient is based upon its distinctive clinical features discerned from the patient’s medical history and neurologic examination. At a minimum, bradykinesia coupled with either tremors or rigidity must be present in order to consider diagnosing a person with PD.